Interpretation of manifest excess of powers with regard to jurisdictional and applicable law matters in the ICSID annulment proceedings within the meaning of Article 52(1)(b) of the ICSID Convention - Šlejs, Dmitrijs (Riga Graduate School of Law, 2019)
There are a limited number of post-award remedies available, the annulment mechanism being the only plausible way to challenge the award. The annulment provision, Article 52, allows challenging the award with regard to the procedural matters only. The most frequently ground for annulment is “manifest excess of powers” as listed in the said provision. However it is not identified what errors of a Tribunal fall within this ground, as well as there is nothing about applicable law and jurisdictional matters in the provision. The thesis aims to analyze how the “manifest excess of powers” is interpreted and applied with regard to jurisdictional and applicable law matters. While some of the errors relating to applicable law and jurisdiction could constitute “manifest excess of powers”, the other do not for reasons elaborated on by the ad hoc Committees. The ad hoc Committees are often criticized for their lengthy commentary which sometimes crosses the thin borderline between appeal and annulment.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International private law and international procedural law; ICSID awards; International arbitration